Association of dietary pattern on asthma and allergic disorders: an observational hospital based study - Dash, Dillip Kumar; Dash, Mrutunjaya; Dash, Bibhudatta; Mohanty, Mamata Devi; Bisoi, Swarup Kumar (International Journal of Contemporary Pediatrics, 2016)
Background: Asthma is an increasing global health burden, especially in the western world but now a day not uncommon in developing countries like India. With rapid changes in diet being one of the hallmarks of westernization, nutrition may play a key role in affecting the complex genetics and developmental pathophysiology of asthma. People consume a combination of foods from various groups that form a dietary pattern. Studying the role of dietary patterns in asthma is an important emerging area of research. The aim of this study was to review dietary patterns and asthma outcomes in children, also to maternal diet and child asthma. With all the studies that have been undertaken, some clearly state the protective effects/adverse effects of certain foods, while others deepen the dilemma. The objective of this study was to establish association between dietary habits and Asthma (and allergic disorders) in children. Methods: A questionnaire obtained from the International study for Asthma and Allergy in Children questionnaire was used to evaluate the dietary habits and disease status of the 834 children attending to pediatrics OPD/IPD for varying disease condition of eastern Odisha region over a period of 2 years. Children aged 4 to14 years with diagnosis of asthma were eligible for the study. The clinical criteria for diagnosis of asthma were based on the recommendations of the British Thoracic Society Guidelines, October 2014. The diagnosis of asthma was made if all the following criteria were met: (i) recurrent episodes (>3) of one or more of the following symptoms - wheeze, cough, breathing difficulties and chest tightness, particularly at night or in the early hours of the morning; (ii) respiratory symptoms improve spontaneously or after treatment (bronchodilators with or without corticosteroids); (iii) presence of triggers or aggravating factors such as exposure to allergens or irritants, physical exercise, weather changes or emotional stress; and (iv) personal history of atopy (allergic rhinitis or eczema) and/or family history of atopy (asthma, allergic rhinitis or eczema) in first-degree relatives. The children/ parental had to fill the questionnaire under teachers’ guidance. Results: Present study reveals asthma and allergic disorders were more prevalent in those consuming a lacto ovo vegetarian diet. Other significant association was seen with Junk food significantly correlated (OR: 1.643, P <0.005), positive family history (P < 0.005) and as well as with obesity (P < 0.005). Conclusions: Although it is common belief that vegetarians are less affected by asthma and other allergic disorder which is backed up by numerous previous studies which reveals a vegetarian diet to be protective against asthma. But our study shows a different picture. The school of thought that considers vegetarian diet tobe protective may lay its basis on the high antioxidant levels in the blood, which according to a new hypothesis, on the contrary may be related to increased risk of allergies too.